The Concept of Mind - Ryle, Gilbert (London Penguin Classics, 2000)
The Concept of Mind (1949) is a book by the philosopher Gilbert Ryle. It argues that the concept of "mind" is "a philosophical illusion hailing chiefly from Descartes and sustained by logical errors and 'category mistakes' which have become habitual."[1] Bryan Magee writes that Ryle derived not only his central thesis, but the essentials of the subsidiary theses, from Arthur Schopenhauer, whose works he had read as a student, then largely forgotten. Ryle, who believed that his theory was original, only realized that he had recycled Schopenhauer when someone pointed it out to him after The Concept of Mind's publication.[2]Stuart Hampshire comments in a review of The Concept of Mind that, "There is only one property which I can discover to be common to Professor Ryle and Immanuel Kant; in both cases the style is the philosopher - as Kant thought and wrote in dichotomies, Professor Ryle writes in epigrams. There are many passages in which the argument simply consists of a succession of epigrams, which do indeed effectively explode on impact, shattering conventional trains of thought, but which, like most epigrams, leave behind among the debris in the reader's mind a trail of timid doubts and qualifications."[3] The book's style of writing was commented on more negatively by Herbert Marcuse, who observes that the way in which Ryle follows his presentation of "Descartes' Myth" as the "official doctrine" about the relation between body and mind with a preliminary demonstration of its "absurdity" which evokes "John Doe, Richard Roe, and what they think about the 'Average Taxpayer'" shows a style that moves "between the two poles of pontificating authority and easy-going chumminess", something Marcuse finds to be characteristic of philosophical behaviorism.[4]David Stannard attributes to Ryle the view that the psychoanalytic idea of the unconscious is rooted in the Cartesian conception of a body-mind dichotomy and as such is one version of "the dogma of the Ghost in the Machine" that Ryle tries to expose. According to Stannard, Ryle views the dogma as a "logical howler" that derives its existence from a category mistake.[5]Richard Webster praises The Concept of Mind's "lucidity and vigour", but suggests that while Ryle's arguments effectively dissolve the mind-body problem, they have failed to bring about a revolution in human knowledge because Ryle's case that the remaining subjective aspects of our experience, consisting of our sensations, memories, consciousness and sense of self, are not the essence of "mind" has not been universally accepted by contemporary philosophers, neuroscientists, and psychologists. Webster sees Ryle's willingness to accept the characterization of The Concept of Mind as behaviorist as misrepresenting its more nuanced position, writing that Ryle's acceptance of that description is far from "harmless", as Ryle himself suggested. Webster stresses that Ryle "does not seek to deny the reality of what we frequently term 'internal' sensations, thoughts or imaginings. He merely denies that these belong to a realm which is logically distinct from, and independent of, the 'external' realm of ordinary human behaviour."[1]John Searle, who believes that no great work of philosophy contains many footnotes and that philosophical quality varies inversely with the number of bibliographical references, considers the absence of footnotes in The Concept of Mind a sign of its quality
Keywords: Philosophy